2017
DOI: 10.1111/cogs.12549
|View full text |Cite
|
Sign up to set email alerts
|

Symbol Grounding Without Direct Experience: Do Words Inherit Sensorimotor Activation From Purely Linguistic Context?

Abstract: Theories of embodied cognition assume that concepts are grounded in non-linguistic, sensorimotor experience. In support of this assumption, previous studies have shown that upwards response movements are faster than downwards movements after participants have been presented with words whose referents are typically located in the upper vertical space (and vice versa for downwards responses). This is taken as evidence that processing these words reactivates sensorimotor experiential traces. This congruency effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
59
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 76 publications
(208 reference statements)
9
59
2
Order By: Relevance
“…Participants. Adapting the sample size determined by Günther et al (2018), we tested 49 native German speakers (9 identified as male, 40 as female, M Age = 23.4 years, S D Age = 3.8 years). One additional participant was not included in the analysis due to a high error rate (see the Results section).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants. Adapting the sample size determined by Günther et al (2018), we tested 49 native German speakers (9 identified as male, 40 as female, M Age = 23.4 years, S D Age = 3.8 years). One additional participant was not included in the analysis due to a high error rate (see the Results section).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…Additionally, we employed eight different Germansounding novel words (Fente, Essede, Seige, Mende, Emahte, Greites, Gehaff, Riehrer) that were already used in the experiments by Günther et al (2018) and were not a priori associated to a vertical dimension. We constructed eight different learning items for each participant by randomly pairing these novel words with the eight novel concepts and their short descriptions (see Table 1 for examples).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, in language processing, the linguistic stimuli would act as cues to re-activate this sensorimotor experience, or the representation formed from it. Although language typically encodes many aspects of the perceptual world, and languagebased representations can come a long way in approximating this perception-based experience (Louwerse, 2011), such redundancies are surely not perfect, and therefore not having direct access to sensorimotor experience will ultimately result in different conceptual representations and processing (Günther, Dudschig, & Kaup, 2018;Kim, Elli, & Bedny, 2019;Striem-Amit, Wang, Bi, & Caramazza, 2018).…”
mentioning
confidence: 99%
“…One prime example are abstract words such as libertarianism, jealousy, or childhood, which by definition do not refer to a distinct class of physical objects (for an overview, see Borghi et al, 2017). However, it should be noted that these issues already arise for concrete words whose referents one has never experienced directly, such as Atlantis or supernova (Günther, Dudschig, & Kaup, 2018;Günther, Nguyen, et al, 2020). The question of how can we achieve grounding in the absence of any direct sensorimotor experience is of central importance for theories of grounded cognition (Borghi et al, 2017); if they can account for only a fraction of words that are directly experienced, the usefulness and adequacy of grounded cognition theories as a generallevel cognitive theory stands in question.…”
mentioning
confidence: 99%